NOISE CHARACTERISTICS OF SEA WAVES BASED ON ITS HEIGHT, PERIOD AND BREAKING WAVES - Amron (Prodi Fisika FST UNJA, 2020)
ABSTRACT Wave sound is one of the sources of ambient noise in the waters which causes the role of sound as a transmission medium of information and communication becomes disrupted. The characteristics of wave noise can be influenced by their parameters, such as height and period of the waves and breaking waves. The study aimed to determine the characteristics of noise (intensity, frequency, pulse duration and interval duration) of waves based on its height, periods and breaking waves. Data acquisition for sound wave is obtained by hydrophones, visual of wave from CCTV cameras, and wave parameters is determined from ADCP data. Sound characteristics based its height, period and breaking waves were analyzed by Kruskal-Wallis analysis. The intensity of noise is affected by all wave parameters, while the pulse duration is significantly influenced by the changes in height and wave period, and the breaking waves velocity. Frequency of noise is only impacted by the breaking wave height. Other noise characteristics, the interval duration is not significantly influenced by all wave parameters.